Rating dan Share pada Program Super Deal Indonesia 2022 di GTV - Arumsari, Mila; Yoedtadi, Moehammad Gafar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Television is one of the mass media sources of information. Producers have an important role in making a television programme so that it can produce the targeted rating and share. There are three important parts in the production of a programme: pre-production, production, and post-production. In these three stages, the producer plays a role in organising all his responsibilities. This research was conducted to find out how the process a producer goes through in handling a television programme so that it can increase ratings and shares. This research uses a qualitative approach with a case study method. Data collection techniques through interviews with producers and executive producers of the